O exerc??cio do filosofar na elabora????o de programas de r??dio - Santana, Jefferson de Souza (2018)
This dissertation aims to understand radio as a philosophical exercise. It examines the process of production of communication in Philosophy classes of a public school in the State of S??o Paulo, located in Jardim das Flores neighborhood, in Osasco, with high school students since the year 2014. The terminology analyzed in this dissertation was carefully selected taking into account the explorations, observations and experiences transcribed in an academic vocabulary so that the reader understands the feeling of a problematizing research spirit. Its objective were to analyze radio as a resource of communication that collaborates for the exercise of philosophizing in Philosophy classes. The research reasoning is conducted through the experience of ???Cala-Boca J?? Morreu Project ??? because we also have something to say!???, which has been working with education through the media for 22 years, and the creation of Radio Latorre, a school project idealized in Philosophy classes whose goal is to change the student role from technology consumer to content producer.